Visualization of Village Fund Budget Realization to Improve Transparency of Information to the Community - Syahrullah, Syahrullah; Lapatta, Nouval Trezandy; Rinianty, Rinianty; Hernita, Ayu; Supardi, Nurhikmah (Jurnal Abmas Negeri (JAGRI), 2025)
Generally, village fund information is delivered in manual format or through printed materials. This type of information delivery is difficult for certain groups to understand, resulting in low community participation in village development planning and evaluation. A new approach is needed, involving the application of information technology through the visualization of village fund planning and budget realization data. This community service program aimed to increase the transparency of village fund management through training in data visualization of planning and budget realization, thereby providing village officials, neighborhood associations, family welfare programs, youth organizations, and young people with an understanding of the importance of information disclosure and the skills to process budget data digitally. The activities are carried out through a combination of theory, practice, group discussions, and monitoring and evaluation. Participants were trained to use Microsoft Excel to present data in the form of infographics, tables, and diagrams that are easy to understand. In this way, the community can obtain a clearer picture of village fund management. The community service activity was designed to last for 6 months (June to November 2025) and the training was conducted over 2 days with a duration of 10 hours, divided into 5 hours per day. The results of the activity showed an average increase in participants’ knowledge and skills of 34 points. This activity can improve participants’ skills and knowledge in visualizing village fund planning and realization data.